2018
DOI: 10.4047/jap.2018.10.5.381
|View full text |Cite
|
Sign up to set email alerts
|

Influence of abutment height and convergence angle on the retrievability of cement-retained implant prostheses with a lingual slot

Abstract: PURPOSECement-retained implant prostheses can lack proper retrievability during repair, and residual cement can cause peri-implantitis. The purpose of this in vitro study was to evaluate the influence of abutment height and convergence angle on the retrievability of cement-retained implant prostheses with lingual slots, known as retrievable cement-type slots (RCS).MATERIALS AND METHODSWe fabricated six types of titanium abutments (10 of each type) with two different heights (4 mm and 6 mm), three different con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…In addition, considering the abutment wall (cylindrical vs. hexagonal), the cast copings cemented on hexagonal 4 mm abutments showed the highest VMD using zinc oxide noneugenol and glass ionomer. Previous studies [22][23][24] showed that the removal forces of cemented copings depend on abutment geometry and luting agents. us, it seems that these two variables are related to technical factors and implant treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, considering the abutment wall (cylindrical vs. hexagonal), the cast copings cemented on hexagonal 4 mm abutments showed the highest VMD using zinc oxide noneugenol and glass ionomer. Previous studies [22][23][24] showed that the removal forces of cemented copings depend on abutment geometry and luting agents. us, it seems that these two variables are related to technical factors and implant treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Bridges 1 and 2 are the only ones with non-tapered abutments on both ends, and the results are in accordance with the established relationship between the abutment taper angle and the coping retrievability. Indeed, it is well-known, from both experimental [30][31][32] and clinical [29] studies, that the abutment retentiveness increases with its height and decreases with its taper angle. On the other hand, bridge 4 was the only one with two 5 mm high and tapered abutments (i.e., a poorly retentive geometry), and it behaved, as expected, as the least retentive one with all cements.…”
Section: Discussionmentioning
confidence: 99%
“…Choi et al demonstraram que a recuperabilidade da prótese final pode ser obtida pelo controle do ângulo de convergência do pilar de acordo com sua altura e presença de slots linguais. Recomendou-se a utilização de cimentos permanentes 17 , porém as limitações do desenho do estudo incapacitam a avaliação de peri-implantite e consequências biológicas de tal aspecto.…”
Section: Revisão Da Literaturaunclassified